P081 Sclerostin affects rankl-mediated osteoclast differentiation. (21st February 2018) - Intemann, J; Wehmeyer, C; Kracke, V; Werbenko, E; Paruzel, P; Kramer, I; Kneissel, M; Pap, T; Dankbar, B
Abstract : Introduction: Sclerostin is a Wnt inhibitor and has anti-anabolic effects on bone formation by negatively regulating osteoblast differentiation. The lack of sclerostin in humans and mice leads to a higher bone mass and bone strength known as sclerosteosis. Therefore, inhibition of sclerostin is currently investigated as a treatment against osteoporosis. Surprisingly, the genetic deficiency or pharmacological inhibition of sclerostin causes a deterioration of disease severity in a TNFα-dependent arthritis mouse model (hTNFtg). hTNFtg mice lacking sclerostin displayed enhanced joint inflammation, cartilage loss and bone erosion associated with an elevated number of osteoclasts within the joint. Objectives: We want to investigate the impact of sclerostin on osteoclast differentiation and bone erosion in arthritis. Methods: Sclerostin knockout (sost -/- ) mice were crossbred with hTNFtg mice to obtain sost -/- /hTNFtg synovial fibroblasts. Co-cultures of synovial fibroblasts and wildtype bone marrow macrophages were analysed by TRAP staining. RANKL expression was measured by ELISA and cytokine expression by array analysis and Western Blot. Moreover, the influence of sclerostin on osteoclastogenesis was additionally analysed in mono-cultures. Results: In our co-culture system of synovial fibroblasts and bone marrow derived macrophages, fibroblasts from sost -/- /hTNFtg mice strongly promote osteoclastogenesis in comparison to hTNFtg synovial fibroblasts. Notably, no increased expression of receptor activator of NF-kB ligand (RANKL) was detectable in sost -/- /hTNFtg fibroblasts even after stimulation with inflammatory cytokines. Interestingly, basal secretion of IL-1α, which is known to stimulate osteoclastogenesis, was higher in sost -/- /hTNFtg compared to hTNFtg fibroblasts. Accordingly, sclerostin inhibited osteoclastogenesis when administered in the pre-differentiation phase, whereas no effect was observed in the differentiation phase, indicating an inhibitory effect of sclerostin on osteoclast precursors. Conclusions: Sclerostin deficiency in hTNFtg synovial fibroblasts promotes RANKL-mediated osteoclastogenesis, which is most likely dependent on IL-1α. Disclosure of interest: None declared